Development of an automated radiation control system based on semiconductor ionizing radiation detectors - Gubarev, S.P.; Klosovsky, A.V.; Leonovych, A.V.; Opaleva, G.P.; Taran, V.S.; Zolototrubova, M.I. (Вопросы атомной науки и техники, 2018)
An automated radiation monitoring system for experimental setups with electromagnetic retention of plasma is presented. It is based on a real-time X-ray measuring device made from available elements. It includes a high-speed integrated microcontroller. The sensor is a semiconductor detector of ionizing radiation with a unit of thermal stabilization.